2003
DOI: 10.1111/1469-7610.00197
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral impulsivity paradigms: a comparison in hospitalized adolescents with disruptive behavior disorders

Abstract: Despite the initiation of pharmacotherapy within the first 3 days of hospitalization, in contrast to the control group, the adolescents with DBD performed consistently with what has been operationally defined as impulsivity. Based on these results, these tasks appear to measure similar, but unique components of the impulsivity construct. With further study, laboratory behavioral paradigms may prove to be useful additions to current clinical diagnostic and treatment procedures in a variety of psychiatric popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
142
0
5

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 147 publications
(151 citation statements)
references
References 66 publications
4
142
0
5
Order By: Relevance
“…To allow comparison on a common scale and prevent domination of variables with large values (i.e., SKIP task), variables were converted to standardized scores (similar to the procedure used in Dougherty et al, 2003b) calculated in two steps. First, a difference score variable was created for each of the active alcohol dose conditions by subtracting the placebo performance data from the peak performance data for each task.…”
Section: Data Analysesmentioning
confidence: 99%
“…To allow comparison on a common scale and prevent domination of variables with large values (i.e., SKIP task), variables were converted to standardized scores (similar to the procedure used in Dougherty et al, 2003b) calculated in two steps. First, a difference score variable was created for each of the active alcohol dose conditions by subtracting the placebo performance data from the peak performance data for each task.…”
Section: Data Analysesmentioning
confidence: 99%
“…Studies have found elevated response initiation impulsivity in adolescents with disruptive behavior disorders (Dougherty et al, 2003a(Dougherty et al, , 2003b(Dougherty et al, , 2007, and in adults with a childhood history of Conduct Disorder (Dougherty et al, 2000). These measures may also be sensitive to individual …”
Section: Response Initiationmentioning
confidence: 99%
“…Conduct Disorder is one of the disorders where impulsivity is especially prominent and severe (Gorenstein & Newman, 1980;Milich & Kramer, 1984;Moeller et al, 2001). Studies have shown how self-reported and behavioral impulsivity are increased among those with CD (Daderman, 1999;Dougherty et al, 2003aDougherty et al, , 2003bTranah, Harnett, & Yule, 1998). In the current study, we were interested in examining performance on the different behavioral measures of impulsivity and how this performance might vary as a function of age of CD onset.…”
mentioning
confidence: 99%
“…13 Precise behaviours that are considered impulsive are very diverse, but they can be categorized into two main aspects of impulsivity: reward-related impulsivity (sensitivity to reward/inability to delay reward) and insufficient inhibitory control over behaviour (the possibility to overrule automatic intentions to respond to stimuli). 13,14 Both impulsive aspects have been linked to obesity. For instance, obese children are more sensitive to reward compared with lean children: they keep gambling for a given reward, even when the chances of winning decrease and stopping would lead to greater gain.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, obese children are more sensitive to reward compared with lean children: they keep gambling for a given reward, even when the chances of winning decrease and stopping would lead to greater gain. 14 Earlier research showed that obese children have an intolerance for delay of gratification. 15 Sensitivity to reward was also found to be related to craving for food and BMI in a female sample.…”
Section: Introductionmentioning
confidence: 99%